2011
DOI: 10.1007/s11606-010-1624-2
|View full text |Cite|
|
Sign up to set email alerts
|

Misuse of Respiratory Inhalers in Hospitalized Patients with Asthma or COPD

Abstract: Inhaler misuse is common, but correctable in hospitalized patients with COPD or asthma. Hospitals should implement a program to assess and teach appropriate inhaler technique that can overcome barriers to patient self-management, including insufficient vision, during transitions from hospital to home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
162
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 160 publications
(174 citation statements)
references
References 29 publications
7
162
1
4
Order By: Relevance
“…Inhaler technique was assessed by a trained RA using detailed checklists for MDI (12-steps) and Diskus® (10 steps). 15 Misuse was defined as <75% of steps correct for each device (<9/12 steps for MDI; <8/10 steps for Diskus®). 15 Because inadequate health literacy is associated with poor inhaler technique, 24,25 participants' health literacy was measured using the Short Test of Functional Health Literacy in Adults (STOFHLA), 26,27 a 36-item written comprehension test (scores: range 0-36); less-than-adequate: <23/36; adequate: ≥23/36.…”
Section: Study Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…Inhaler technique was assessed by a trained RA using detailed checklists for MDI (12-steps) and Diskus® (10 steps). 15 Misuse was defined as <75% of steps correct for each device (<9/12 steps for MDI; <8/10 steps for Diskus®). 15 Because inadequate health literacy is associated with poor inhaler technique, 24,25 participants' health literacy was measured using the Short Test of Functional Health Literacy in Adults (STOFHLA), 26,27 a 36-item written comprehension test (scores: range 0-36); less-than-adequate: <23/36; adequate: ≥23/36.…”
Section: Study Proceduresmentioning
confidence: 99%
“…1) The TTG intervention was chosen based on preliminary results from prior work that demonstrated its success as a hospital-based approach for teaching the use of respiratory inhalers. 15,16 A variety of alternative comparators were considered, including usual care. Because usual care may vary by institution and provider, a standardized but limited educational strategy, dubbed "brief intervention" (BI) was chosen.…”
Section: Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is salient because research has shown that poor vision can be a separate barrier to self-management, such as the ability to open medication containers, 4 and among hospitalized patients, appropriate inhaler technique. 2 Given these findings, it is important to understand the role of vision for self-management strategies, with respect to assessing health literacy level and/or whether poor vision compounds health risks associated with low health literacy.…”
mentioning
confidence: 99%